Buriti oil emulsions as affected by spi/high-methoxyl pectin ratio, oil content and homogenization pressure: Production and characterization of buriti oil emulsions - Freitas, Mírian Luisa Faria; Ribeiro, Ana Paula Badan; Nicoletti, Vânia Regina [UNESP] (Faculty of Food Technology and Biotechnology - University of Zagreb, 2020)
Research background. Emulsion technology is a suitable way of encapsulating, protecting and releasing bioactive hydrophobic compounds for application in food industries, but they are thermodynamically unstable systems. Good results have been achieved for emulsions stabilized by protein-polysaccharide complexes subjected to high-pressure homogenization. Improved stabilization of oil-in-water emulsions results from electrostatic complexes formed between protein-polysaccharide at pH lower than protein isoelectric point, which adsorb at the oil-water interface. In addition, polysaccharides contribute to emulsion stability by increasing viscosity of the continuous phase. The aim of this work was to investigate the production of carotenoid-rich buriti oil emulsions using soy protein isolate and high-methoxyl pectin as stabilizers. Experimental approach. The effects of oil content, soy protein isolate:high-methoxyl pectin ratio, and homogenization pressure were assessed according to a rotatable central composite experimental design. The emulsions were evaluated regarding stability, droplet size, electrical conductivity, electrical charge, microstructure, and rheological behavior. Results and conclusions. An optimized emulsion was produced with 28 % buriti oil, 55 % soy protein isolate, and homogenization pressure of 380105 Pa. This emulsion was stable for at least seven days, presenting reduced average droplet size, low electrical conductivity and high modulus of negative charges. The mechanical spectra showed that the emulsion behaved as a viscoelastic gel under oscillatory, non-destructive shearing, whereas shear-thinning behavior took place under steady shear conditions. Novelty and scientific contribution. The optimized buriti oil emulsions stabilized by soy protein isolate and high-methoxyl pectin could be suitable for fat substitution, energy reduction, and carotenoid enrichment in food products, such as dairy and bakery products, ice cream, salad sauces, and vegetal cream.
Keywords: Buriti oil; Dispersed systems; Electrostatic interaction; High-methoxyl pectin; Rheology; Soy protein isolate